(3GdfLe GdhgGL aj TQM GdefgGLs - (3eMeO Hf ehSi Hf YjSi GdOejQj GdTGaYj , ceGd GdOjf CHh GdHbGA,J (B808 (3g` s; (3Gdfhhj,J (B676 (3g` s
(3ChdgG (B:s
(3cJGH GdRcGI s
(3BNQgG (B:s
(3cJGH GdbQGV s
(3fSNI QGHYIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdTGaYjs